User evaluations of tax filing web sites A comparative study of South Korea and Turkey - (:unkn) unknown (EMERALD GROUP PUBLISHING LIMITED, 2008)
Purpose - The purpose of this paper is to compare the web-based tax filing systems of Turkey and South Korea. The comparison is based on user satisfaction which has parameters such as ease of work, adequacy of the amount of information, display speed, convenience to life, job productivity, and help service. Design/methodology/approach - The tax filing systems are presented along with a background of such systems and their usability parameters. The survey instrument that has been prepared for gauging user satisfaction was applied to the users in both countries. The statistical analyses of the results are performed through t-test and stepwise regression. Findings - The study shows that users in the two countries felt differently in such factors as ease of work, adequacy of the amount of information, display speed, convenience to life, job productivity, and help service. Although Turkey has a complex tax system Turkish users did not find the tax filing system difficult to use and that may be attributable to the fact that they are accounting professionals who frequently use the system. Practical implications - Electronic tax filing is an important e-government application that has become increasingly common all over the world. Beyond the usual benefits of e-government such as reducing transaction costs and providing convenience, electronic tax filing systems are particularly useful for governments to avoid tax evasion and errors. Although, by definition, web-based tax filing systems of different countries have to be different, universal design parameters of each system and the resulting user satisfaction levels may provide guidelines for new systems. Originality/value - Unlike other types of information systems, which have been comparatively analyzed in the context of more than one country, this is not applicable to e-government systems. To the authors' knowledge the present article is the first attempt to compare and analyze two countries' different e-government systems.
Keywords: Online operations; Taxation; Internet; Turkey; South Korea; INFORMATION-SYSTEMS SUCCESS; E-GOVERNMENT; E-COMMERCE; METRICS; MODEL; TECHNOLOGY; ACCEPTANCE; SERVICES; DELONE